Habituation and novelty detection fNIRS brain responses in 5‐ and 8‐month‐old infants: The Gambia and UK. Issue 5 (13th March 2019) - Lloyd‐Fox, Sarah; Blasi, Anna; McCann, Samantha; Rozhko, Maria; Katus, Laura; Mason, Luke; Austin, Topun; Moore, Sophie E.; Elwell, Clare E.; ,
Abstract: The first 1, 000 days of life are a critical window of vulnerability to exposure to socioeconomic and health challenges (i.e. poverty/undernutrition). The Brain Imaging for Global Health (BRIGHT) project has been established to deliver longitudinal measures of brain development from 0 to 24 months in UK and Gambian infants and to assess the impact of early adversity. Here results from the Habituation‐Novelty Detection (HaND) functional near‐infrared spectroscopy (fNIRS) task at 5 and 8 months are presented ( N  = 62 UK; N  = 115 Gambia). In the UK cohort distinct patterns of habituation and recovery of response to novelty are seen, becoming more robust from 5 to 8 months of age. In The Gambia, an attenuated habituation response is evident: a larger number of trials are required before the response sufficiently suppresses relative to the response during the first presented trials. Furthermore, recovery of response to novelty is not evident at 5 or 8 months of age. As this longitudinal study continues in The Gambia, the parallel collection of socioeconomic, caregiving, health and nutrition data will allow us to stratify how individual trajectories of habituation and recovery of response to novelty associate with different risk factors and adaptive mechanisms in greater depth. Given the increasing interest in the use of neuroimaging methods within global neurocognitive developmental studies, this study provides a novel cross‐culturally appropriate paradigm for the study of brain responses associated with attention and learning mechanisms across early development. Abstract : The Brain Imaging for Global Health (BRIGHT) project has been established to deliver longitudinal measures of brain development from 0‐24 months in UK and Gambian infants. A novel cross‐culturally appropriate functional near infrared spectroscopy (fNIRS) paradigm demonstrated habituation and novelty detection brain responses in 5 and 8 month old infants in the UK. In the Gambia, habituation brain responses were attenuated, and a recovery of response to novelty absent, at the group level, at 5‐8 months of age.